Research on incentive mechanism integrated trust management for P2P networks - HU Jian-li1; ZHOU Bin2; WU Quan-yuan2 (Tongxin xuebao)
An important challenge regarding peers’ trust valuation in peer-to-peer（P2P） systems was how to cope with such issues as dishonest feedbacks from malicious peers,collusions and complicatedly strategic frauds to the trust model itself,which could not be effectively tackled by the existing solutions.Thus,an incentive mechanism integrated trust management model for P2P networks,（IMTM） was proposed,to quantify and evaluate the trustworthiness of peers.Moreover,the related definitions and distributed implementation strategies of IMTM was also given.In IMTM,the recommendation credibility,composed of three factors,including the similarity characteristics,the altering scope of interaction experiences and the time fading feature of trust when interacting,was introduced to portray the extent to which the trustor trusted another recommender’s recommendations.Besides,the trusted service persistent intensity was imported to this model to promote peers to provide high-quality services to others continuously,and the risk mechanism was used to improve the sensitivity of this model.Additionally,based on the trust model,an adaptive reputation based incentive mechanism was presented.Through this mechanism,trusted peers could migrate to the centric position,while untrusted peers to the edge of the topology,incenting peers to provide more high-quality services in order to get more return on services.Theoretical analyses and experimental results demonstrate that IMTM has advantages in combating such malicious behaviors as the dishonest recommendations from malicious peers,collusions and the complicatedly strategic attacks to the trust model itself over the existing models,and show more adaptability,sensitivity and effectiveness.